2014
DOI: 10.3109/13880209.2014.891042
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of clovers – Free radical scavenging ability and antioxidant action of sixTrifoliumspecies

Abstract: Context: Clovers were chosen on the basis of traditional medicine recommendations, agricultural value, or available information on their promising chemical profiles.Objective: This study evaluates and compares free radical scavenging and antioxidant properties of six clover species: Trifolium alexandrinum L. (Leguminosae), Trifolium fragiferum L., Trifolium hybridum L., Trifolium incarnatum L., Trifolium resupinatum var. majus Boiss., and Trifolium resupinatum var. resupinatum L. Materials and methods: Free ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 32 publications
1
22
1
Order By: Relevance
“…Similarly, the ferric reducing abilities of the phenolic fraction of T. pratense and T. pallidum extract were considerably higher than those for T. pratense crude extract and phenolic fraction of T. scabrum (Table 3). Additionally, the EC 50 values obtained for T. pratense, T. pallidum, and T. scabrum from measurements of free radical scavenging tests during this study were compared with results for other six clover species, derived from our earlier experiments (Kolodziejczyk-Czepas et al, 2014). Our comparative analysis of the radical scavenging properties of 10 extracts from Trifolium species indicated that five of them (T. alexandrinum, T. pallidum, T. pratense (phenolic fraction), T. resupinatim var.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the ferric reducing abilities of the phenolic fraction of T. pratense and T. pallidum extract were considerably higher than those for T. pratense crude extract and phenolic fraction of T. scabrum (Table 3). Additionally, the EC 50 values obtained for T. pratense, T. pallidum, and T. scabrum from measurements of free radical scavenging tests during this study were compared with results for other six clover species, derived from our earlier experiments (Kolodziejczyk-Czepas et al, 2014). Our comparative analysis of the radical scavenging properties of 10 extracts from Trifolium species indicated that five of them (T. alexandrinum, T. pallidum, T. pratense (phenolic fraction), T. resupinatim var.…”
Section: Resultsmentioning
confidence: 99%
“…Determination of the TAC of plasma using the FRAP assay was carried out according to modified method of Benzie and Strain (1996) as was described previously (Kolodziejczyk-Czepas et al, 2014). This method was also used for the evaluation of ferric reducing ability of different concentrations of the tested Trifolium extracts, where instead of blood plasma, solutions of these extracts were used.…”
Section: Measurements Of the Ferric-reducing Ability Of Plasma (Frap)mentioning
confidence: 99%
“…A comparative in‐vitro analysis of free radical scavenging properties of extracts from other Trifolium species demonstrated that several clovers might be a source of potent antioxidants. On the other hand, the mentioned works confirmed the importance of individual components for the total antioxidant efficacy of plant extracts.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Trolox V R and (À)-epicatechin) were performed at the concentration range of 1.25-20 lg/mL. Experiments were performed accordingly to the protocol described previously (Kolodziejczyk-Czepas et al 2014). The RSAs of the examined fraction and reference compounds were calculated from the following equation: RSA (%) ¼ 100 Â (A 0 À A 1 )/A 0 .…”
Section: Cytotoxicity Evaluationmentioning
confidence: 99%